Types and tissue sources of bone grafts in dental implants - Haroub, Anas Omar; Edrees, Mustafa Burhan; Misfer, Rema Tariq; Saidi, Khadijah Mustafa; Binjahlan, Meelad Mahmood; Barnawi, Rasha Fahad; Abdullah, Haneen Anis; Aljishi, Hala Nader; Albalawi, Salem Hamed; Alrashdi, Anwar Khunayfir; Shafei, Reem Mohammad (International Journal Of Community Medicine And Public Health, 2021)
Using bone grafts has been described in the literature for multiple decades and has been applied within the different medical fields. Furthermore, in the field of dentistry, evidence shows that these approaches have been widely used for different purposes, including the management of craniofacial defects and dental implantology. However, it should be noted that many disadvantages have been reported for the different tissue sources of bone grafting in dental implants despite the wide acceptance of the outcomes and favorable prognosis with these materials. Therefore, many efforts were conducted to innovate further approaches with reduced disadvantages and favorable outcomes. Our present study discusses the types and tissue sources of bone grafts in the settings of dental implants. This can provide dentists with better information and enhanced knowledge levels about the tissue sources of dental implants, which should help them decide the most appropriate source with the least adverse events. Different tissue sources were reported in the literature, including materials that are no longer used for their disadvantages and associated complications. Among the proposed materials, biomimetics has been reported with favorable outcomes and reduced adverse events, and using combinations of these materials can furtherly enhance the prognosis. Further research is needed to innovate additional modalities that can overcome the currently reported limitations.